Ultrashort Vertical‐Channel van der Waals Semiconductor Transistors. Issue 4 (23rd December 2019) - Jiang, Jinbao; Doan, Manh‐Ha; Sun, Linfeng; Kim, Hyun; Yu, Hua; Joo, Min‐Kyu; Park, Sang Hyun; Yang, Heejun; Duong, Dinh Loc; Lee, Young Hee
Abstract: Atomically thin 2D van der Waals semiconductors are promising candidates for next‐generation nanoscale field‐effect transistors (FETs). Although large‐area 2D van der Waals materials have been successfully synthesized, such nanometer‐length‐scale devices have not been well demonstrated in 2D van der Waals semiconductors. Here, controllable nanometer‐scale transistors with a channel length of ≈10 nm are fabricated via vertical channels by squeezing an ultrathin insulating spacer between the out‐of‐plane source and drain electrodes, and the feasibility of high‐density and large‐scale fabrication is demonstrated. A large on‐current density of ≈70 µA µm −1 nm −1 at a source–drain voltage of 0.5 V and a high on/off ratio of ≈10 7 –10 9 are obtained in ultrashort 2D vertical channel FETs with monolayer MoS2 synthesized through chemical vapor deposition. The work provides a promising route toward the complementary metal–oxide–semiconductor‐compatible fabrication of wafer‐scale 2D van der Waals transistors with high‐density integration. Abstract : Ultrashort vertical‐channel 2D van der Waals semiconductor transistors are fabricated with a controllable channel length of ≈10 nm via 2D vertical channels by squeezing an ultrathin insulating spacer between the out‐of‐plane source and drain electrodes, showing high performance with large on‐current density and high on/off ratio, together with the feasibility of large‐scale and high‐density fabrication.